Quality of Tax Services and Tax Sanctions on Taxpayer Compliance Corporate Listing in KPP Madya Bandung Years 2017-2021 - Wulan Nurbaiti Rahayu Febrian; Kartika Pratiwi Putri; Maria Lusiana Yulianti (Journal of Accounting and Finance Management, 2022)
Taxes are the largest source of state revenue in Indonesia. Tax money paid by the public will be included in state revenue from the tax sector. In 2020 tax revenues have decreased due to the impact of the Covid-19 pandemic because the targets to be achieved are not in accordance with the actual results. The aim of the research is to find out whether the quality and tax sanctions affect the compliance of corporate taxpayers in fulfilling tax regulations. The research method used in this research is descriptive method and the approach used is a quantitative approach. The population in this study were corporate taxpayers registered at KPP Madya Bandung and the sample used was 92 corporate taxpayers. The results of the study concluded that the quality of tax services and tax sanctions partially have a significant positive effect on taxpayer compliance. The quality of tax services and tax sanctions simultaneously have a significant positive effect on taxpayer compliance.